Building control systems of European Union countries: A comparison of tasks and responsibilities - Branco Pedro, J. (2013)
Purpose – The purpose of this paper is to compare the tasks and responsibilities of public and private parties in the building control systems of the 27 European Union (EU) countries. Design/methodology/approach – To gather the necessary information, a questionnaire on building regulatory systems was distributed to experts in each country, and the major legal documents in each jurisdiction were reviewed. The information was organized into thematic tables that describe all the countries studied. The themes within the tables are: regulatory framework, application, plan approval, site inspection, completion, and supervision. Findings – The paper finds that there aremany similarities between the building control systems of the various EU countries. Public parties in all countries set the regulatory framework, check planning applications, issue building permits, conduct final inspections, grant completion certificates, and supervise the operation of the system. The main difference between them concerns the nature of the involvement of private parties in checking technical requirements, and in site inspections. Three basic types of building control systems are identified: public, mixed, and dual. The majority of the countries have mixed systems. Although several variations are found among the mixed systems, the most common situation is for public parties to check the technical requirements and private parties to be involved in site inspections. Originality/value – The analysis provides a global picture of the building control systems of all EU countries. The results can be useful for situating the systems of each country within the European panorama, assessing the main trends and developments and guiding strategic choices on possible improvements in each country.